The Spirit of Biblical Law - Richard Hiers (Washington University Global Studies Law Review, 2002)
In this book reivew, Richard Hiers offers a review of Calum M. Carmichael's, The Spirit of Biblical Law.
Keywords: The Spirit of Biblical Law; Calum M. Carmichael; Religion; Religious law; Legal history